Outcome of Acute Deep Venous Thrombosis Using Standard Treatment versus Thrombolytics: A Literature Review - Abdella Birhan; Tamrat Assefa; Alemseged Beyene; Pacifique Ndayishimiye; Minyahil Alebachew Woldu (International Journal of Hematology-Oncology and Stem Cell Research, 2019)
Deep vein thrombosis (DVT) is a major health problem affecting a significant portion of population. Primary complications are Pulmonary Embolism (PE) in the short term and Post-Thrombotic Syndrome (PTS) in the long term. Thrombolytic drugs act by activating plasminogen which in turn forms the enzyme plasmin. Plasmin consequently degrades blood clots by breaking down the fibrin molecules which make up the clots help to degrade the already formed clot. They can be used using different route of administration, doses and durations. The purpose of this systematic review was to assess the outcome of thrombolytic therapy in terms of the efficacy, safety and effectiveness of the medicines. Electronic searches of databases (MEDLINE and Google Scholar) were queried for articles written in English since 2000 GC. A total of 760 results were obtained using the search keys, and after excluding duplicates, 275 articles were selected. Finally, 9 randomized controlled trials (RCTs) which met the language of publication, study design and exclusion criteria were included in this systematic review. The data were obtained from nine trials (6 countries), providing a study-level data of 1309 participants. Almost all studies revealed that thrombolytic treatment was effective in the management of acute DVT. In most of the studies, the rate of rethrombosis was lower in case of thrombolytic than standard management. Hence, addition of thrombolytic results in persistence and increases the clinical benefits. Thrombolytic therapy was very effective in reversing closed veins, in boosting the patency rate, while reflux was higher in patients treated with anticoagulants. Thrombolytic offers potential advantages over the standard treatment of DVT by reducing the proportion of patients with chronic disabling leg symptoms (such as PTS) by triple in the longer term. However, the incident of major bleeding was higher in patients receiving thrombolytics